DETERMINAN PERILAKU ETIS PEGAWAI - Sugiarti Sugiarti; Eko Madyo Sutanto (Riset Manajemen dan Akuntansi, 2020)
The research aims to examine the causalities relationship between the intern control system and reward. The research method used with regression analysis. This research shows that reward can improve employee ethical behavior because internal control policies cannot improve employees’ ethical behavior. Human resource problems are still the main concern and support for companies to remain able to survive in the era of globalization. In order to improve the ethical behavior of an employee, it is emphasized the need for study policies regarding ethical issues. The sample in this study are employees who are civil servants in BPPKAD Surakarta. The purpose of this study is to determine the ethical behavior of employees who are influenced by the internal control system and reward. All data analysis techniques in this study used multiple linear regression and were carried out with the help of SPSS program. The results of this study are that the internal control system does not affect the ethical behavior of employees. While rewards affect employee ethical behavior. This shows that the internal control system policy has not been able to influence ethical behavior and the policy of increasing or decreasing rewards will have an impact on expected ethical behavior